1) х²-12х+16=0; 2) x²-28x+16=0; 3) x²-14x+44=0
Пошаговое объяснение:
По теореме Виета для приведенного квадратного уравнения:
{х1+х2= -b= 6
{x1x2= c= 4
1) х'1=2х1, х'2=2х2
{х'1+х'2= 2х1+2х2= 2(х1+х2)
{х'1х'2= 2х1×2х2= 4х1х2
{2(х1+х2)= 6×2= 12= -b'
{4x1x2= 4×4= 16= c'
х²-12х+16=0
2) х'1=х1², х'2=х2²
{х'1+х'2= х1²+х2² = (х1)²+2х1х2+(х2)²-2х1х2= (х1+х2)²-2х1х2
{х'1х'2= х1²х2²= (х1х2)²
{(х1+х2)²-2х1х2= 6²-2×4= 28= -b'
{(x1x2)²= 4²= 16= c'
x²-28x+16=0
3) x'1=x1+4, x'2=x2+4
{x'1+x'2= x1+4+x2+4= x1+x2+8
{x'1x'2=(x1+4)(x2+4)= x1x2+4x1+4x2+16= x1x2+4(x1+x2)+16
{x1+x2+8= 6+8= 14 = -b'
{x1x2+4(x1+x2)+16= 4+4×6+16= 44= c'
x²-14x+44=0
1)450+500=960;960-500=460; 960-460=500;
2)90+80=170; 170-80=90; 170-90=80,
3)870-50=820; 820+50=870 ;
4)180-90=90; 90+90=180;
5)540-300=240; 240+300=540
6)830+70 =900; 900-70=830; 900-830=70;
7)459-9=450 ;450+9=459
8)709+80=789; 789 -80=709; 789-709=80
9)89+700==789; 789-700=89; 789-89=700
10)540-500=40; 40+500=540;
11)290-90=200; 200+90=290;
12)750-300=450; 450+300=750;